SHREC'16: Partial matching of deformable shapes - Cosmo, L.; Rodolà, E.; Bronstein, M. M.; Torsello, A.; Cremers, D.; Sahillioǧlu, Y. (Eurographics Workshop on 3D Object Retrieval, EG 3DOR, 2016)
Matching deformable 3D shapes under partiality transformations is a challenging problem that has received limited focus in the computer vision and graphics communities. With this benchmark, we explore and thoroughly investigate the robustness of existing matching methods in this challenging task. Participants are asked to provide a point-to-point correspondence (either sparse or dense) between deformable shapes undergoing different kinds of partiality transformations, resulting in a total of 400 matching problems to be solved for each method - making this benchmark the biggest and most challenging of its kind. Five matching algorithms were evaluated in the contest; this paper presents the details of the dataset, the adopted evaluation measures, and shows thorough comparisons among all competing methods.
CRIS-Team Scopus Importer:2023-03-08